Board Game “Colonial War” Sebagai Media Edukasi Sejarah Perang Gerilya Jenderal Soedirman Untuk Anak SD Usia 10-13 Tahun - Kusumohendrarto, Raden Hadapiningrani; Nadifah, Alvina (Jurnal Serambi Ilmu, 2024)
History is a very important thing for a country, and in Indonesia, there is a history of guerrilla war led by General Soedirman as resistance to the Dutch, who did not recognize Indonesian independence. However, today's elementary school children don't really like history lessons because they consider them boring, including lessons on the history of General Soedirman's guerrilla war. The use of educational media has now developed to the point where board games are used as educational media to convey messages that are packaged in an attractive way. The method used in this design is “design thinking”, with five stages: empathize, define, ideate, prototype, and test. This research will design interactive board game media for the learning process of the history of General Soedirman's guerrilla war to make it more effective, active, and communicative. and it is hoped that it can increase students' enthusiasm for knowing the history of Indonesia and forming good personalities.